Health condition and job status interactions: Econometric evidence of causality from a French longitudinal survey - Eric Delattre; Richard K. Moussa; Mareva Sabatier (Health Economics Review, 2019)
This article investigates the causal links between health and employment status. To disentangle correlation from causality effects, the authors leverage a French panel survey to estimate a bivariate dynamic probit model that can account for the persistence effect, initial conditions, and unobserved heterogeneity. The results highlight the crucial role of all three components and reveal strong dual causality between health and employment status. The findings clearly support demands for better coordination between employment and health public policies.
Keywords: I10; J6; C3; C51; 330; Health and job causality; Bivariate dynamic probit model; Gauss-Hermite quadrature